Market competition and executive pay - Priscila Ferreira (IZA World of Labor, 2019)
Deregulation and managerial compensation are two important topics on the political and academic agenda. The former has been a significant policy recommendation in light of the negative effects associated with overly restrictive regulation on markets and the economy. The latter relates to the sharp increase in top executives' pay and the nature of the link between pay and performance. To the extent that product-market competition can affect the incentive schemes offered by firms to their executives, the analysis of the effects of competition on the structure of compensation can be informative for policy purposes.
Keywords: J31; J33; M52; 330; barriers to entry; entry costs; competition; executive compensation; performance-related pay